Survey of Rainwater Catchment Use and Practices on Hawaii Island. (5th September 2017) - Donohue, Mary J.; Macomber, Patricia S.H.; Okimoto, Darren; Lerner, Darren T.
Abstract: The harvesting of rainwater for domestic use on Hawaii Island is widespread, particularly in areas not served by municipal water. Rainwater catchment is currently unregulated in Hawaii with the responsibility of installing and maintaining appropriate systems on owners and users. Well‐designed and maintained rainwater catchment systems are more likely to provide water free of pathogens than poorly designed or maintained systems. We conducted outreach to rural Hawaii Island communities on rainwater catchment best practices and explored household uses and practices associated with these systems via survey of 110 individuals. Nearly 90% (N=96) of all survey respondents used harvested rainwater as a potable water source or for bathing, and we estimate only 66% of those systems may reasonably be expected to produce safe drinking water. Reported testing frequency of captured rainwater falls below recommended levels and varies significantly with rainwater use and system adequacy. Outreach was effective in changing perceptions on rainwater catchment as evidenced by individuals' reported beliefs before and after engagement. The majority (N=75) of all survey respondents reported they will change how they maintain their catchment systems, and over 50% (N=61) reported they will change their catchment system elements, as a result of outreach. We conclude there is a demonstrated need for ongoing, professional, evidence‐based outreach programs to serve rainwater catchment system users in Hawaii.